NUMERICAL STUDY OF DIFFUSER EFFECT ON BLUFF BODY : AERODYNAMIC CHARACTERISTICS - M. Yasep Setiawan; Martias Martias; Erzeddin Alwi (Universitas Sultan Ageng Tirtayasa, 2017)
This study focuses on the numerical study of flow structure analysis around bluff bodies close to the downstream face of the free-channel surface. This was investigated using coefficient pressure, coefficient drag, lift coefficient and skin friction coefficient on high Reynolds number (ReH = 2.19 × 106). The general procedure for this research is formulated in detail for allocations in dynamic analysis of fluid computing. The numerical model used is the 2D RANS model (Steady Reynolds Averaged Navier Stokes) with the standard k-ɛ model by giving a flow rate of 40 m / s. This bluff body model will be given the addition of diffuser treatment on the back where the result will be compared to the model without the addition of diffuser and the addition of round shape on the top front on both models. From the research it was found that the coefficient drag bluff body with the addition of diffuser is bigger than the bluff body without the diffuser, it can be concluded that the diffuser angle used is too big causing the coefficient drag to become bigger.